2014
DOI: 10.1371/journal.pone.0086119
|View full text |Cite
|
Sign up to set email alerts
|

Structural Integrity of the Contralesional Hemisphere Predicts Cognitive Impairment in Ischemic Stroke at Three Months

Abstract: After stroke, white matter integrity can be affected both locally and distally to the primary lesion location. It has been shown that tract disruption in mirror’s regions of the contralateral hemisphere is associated with degree of functional impairment. Fourteen patients suffering right hemispheric focal stroke (S) and eighteen healthy controls (HC) underwent Diffusion Weighted Imaging (DWI) and neuropsychological assessment. The stroke patient group was divided into poor (SP; n = 8) and good (SG; n = 6) cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 75 publications
5
49
0
1
Order By: Relevance
“…38 Similarly, in a cohort of patients with right hemispheric ischemic stroke, with the use of Tract Based Spatial Statistics, FA values in the specific regions of the contralateral hemisphere correlated with performance on neuropsychological testing. 33 Our data now offer new evidence to demonstrate the utility of global measures of WM integrity in this population.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…38 Similarly, in a cohort of patients with right hemispheric ischemic stroke, with the use of Tract Based Spatial Statistics, FA values in the specific regions of the contralateral hemisphere correlated with performance on neuropsychological testing. 33 Our data now offer new evidence to demonstrate the utility of global measures of WM integrity in this population.…”
Section: Resultsmentioning
confidence: 61%
“…7,27,[29][30][31] Thus, it seems intuitive that WM integrity would influence poststroke recovery. 3,4,[32][33][34][35] The exact mechanisms by which prestroke WM integrity might influence poststroke functional recovery are yet to be determined; however, data that underscore the role of structural connectivity in functional performance in general populations point in the direction of potential underlying pathology. 7,21 Therefore, more severe total pre-AIS burden of WM disease (including overt WMH and microstructural injury in NAWM) may signify a degree of subclinical baseline cognitive and functional decline that predisposes these individuals for less favorable recovery after AIS.…”
Section: Resultsmentioning
confidence: 99%
“…TBSS can reduce the effects of local misregistrations by projecting all FA voxels onto the nearest location on a "skeleton" approximating WM tract center [9] [12] [13]. So TBSS has become a kind of popular software to study DTI, and has been used in some studies of various diseases, such as stroke [14], Parkinson [15], epilepsy [16], multiple sclerosis [17], traumatic brain injury [18], schizophrenia [19] and so on. Also some studies of cognitive disorders used TBSS, included mild cognitive impairment (MCI) and AD [9] [20].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Besides remote structural changes in the ipsilesional hemisphere, a few small neuroimaging studies (6-16 patients) in older patients with stroke (≥60 years) found loss of white matter integrity as remote as the contralesional hemisphere, 13 and this was associated with motor impairment ≤6 months after stroke 14,15 and poorer cognitive recovery 3 months after right middle cerebral artery stroke. 16 It is unknown whether lower microstructural integrity in areas remote from the initial stroke, including as remote as the contralesional hemisphere, is related to long-term (ie, years) cognitive dysfunction after stroke. In addition, the presence of preexisting (subclinical) cerebral small vessel disease, such as diffuse white-matter hyperintensities or subclinical infarcts, may also contribute to the poststroke spectrum of cognitive impairment 6 …”
mentioning
confidence: 99%